Perlindungan Pelaku Usaha Terhadap Penggunaan Foto Produk Tanpa Izin di Marketplace Tokopedia Perspektif Fatwa MUI Nomor 24 Tahun 2017 Tentang Pedoman Bermuamalah di Media Sosial - Zeta Donita, Zahra; Sativa, Annisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Product photos play a crucial role in today’s digital trade as they serve as a visualization of goods, function as a marketing strategy, and assist consumers in making purchasing decisions. However, due to the ease of access provided by the internet, many business actors face problems, one of which is the misuse of product photos by other parties without the owner’s consent, which may harm business actors and create unfair competition. This study aims to analyze the legal protection available to business actors against the unauthorized use of product photos on the Tokopedia marketplace and to examine this issue from the perspective of the Indonesian Ulema Council (MUI) Fatwa No. 24 of 2017 concerning Guidelines for Interaction in Social Media. The research employs a normative legal method with a conceptual approach and utilizes two types of data sources, namely primary and secondary. The findings indicate that product photos are creative works protected under the Copyright Law, and their unauthorized use constitutes a violation. Tokopedia has provided an intellectual property (IP) reporting mechanism and imposes sanctions on the unauthorized use of product photos. From the perspective of MUI Fatwa No. 24 of 2017, such actions are prohibited (haram) as they are considered misleading, deceitful, infringing upon intellectual property rights, and causing harm. The study concludes that the unauthorized use of product photos constitutes a violation of both positive law and Islamic law. Although legal protection for business actors is already available, greater dissemination of the MUI fatwa and consumer education are necessary to foster a fair and trustworthy digital marketplace.